2023
DOI: 10.1186/s12864-023-09581-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and characterization of Helcococcus ovis: a comprehensive comparative genomic analysis of virulence

Federico Cunha,
Segundo Casaro,
Kristi L. Jones
et al.

Abstract: Background Helcococcus ovis (H. ovis) is an emerging bacterial pathogen that commonly causes opportunistic respiratory, mammary, and uterine infections across mammalian hosts. This study applied long- and short-read whole genome sequencing technologies to identify virulence factors in five H. ovis isolates with low, medium, and high virulence phenotypes. Results The resulting assemblies contained one circular chromosome ranging from 1,744,566 to 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…This strain displayed an atypical biochemical profile for H. ovis and a 98.9% 16S rRNA sequence identity with the H. ovis type strain, which led researchers to question its place within the species taxon. Phylogenomic analyses have shown that, based on 16S rRNA sequence identity, the Tongji strain belongs to a subclade of the species also populated by H. ovis strain KG38 (15). Whole genome-based multi-locus phylogenomic analyses in this study confirmed these findings and identified three further strains (KG95, KG105, and KG197) belonging to the cryptic clade.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This strain displayed an atypical biochemical profile for H. ovis and a 98.9% 16S rRNA sequence identity with the H. ovis type strain, which led researchers to question its place within the species taxon. Phylogenomic analyses have shown that, based on 16S rRNA sequence identity, the Tongji strain belongs to a subclade of the species also populated by H. ovis strain KG38 (15). Whole genome-based multi-locus phylogenomic analyses in this study confirmed these findings and identified three further strains (KG95, KG105, and KG197) belonging to the cryptic clade.…”
Section: Discussionsupporting
confidence: 77%
“…As shown in an invertebrate infection model, H. ovis strains originating from the uterus of dairy cows can display varying degrees of virulence (14). Based on the virulence phenotypes from that study, whole genome comparative analyses identified potential high virulence determinants in this organism, including Zinc ABC transporters, two hypothetical proteins, and a pathogenicity island (15). These comparative analyses created a blueprint for investigating H. ovis pathogenic capabilities, but the role these virulence factors may play in disease pathogenesis remains unexplored.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations